Improving Bi-Objective Shortest Path Search with Early Pruning. - Mandow-Andaluz, Lorenzo; Pérez-de-la-Cruz-Molina, José Luis (My University, 2023)
Bi-objective search problems are a useful generalization of shortest path search. This paper reviews some recent contributions for the solution of this problem with emphasis on the efficiency of the dominance checks required for pruning, and introduces a new algorithm that improves time efficiency over previous proposals. Experimental results are presented to show the performance improvement using a set of standard problems over bi-objective road maps.
Keywords: Programación heurística; Algoritmos; Multiobjective search; Graph search; Shortest path problem; Heuristic search